Effect of boron on the structure and tensile property of Ti6Al4V produced by VAR and free forging. (May 2015) - He, T.; Feng, Y.; He, Y. S.; Lai, Y. J.; Luo, W. Z.; Wang, W. D.; Du, J. C.
Abstract : It has been proven that trace boron additions ( ≤ 0·4 wt-%) to titanium alloys can refine the as-cast microstructure significantly and improve the alloys' mechanical performance. This paper studied the structure of Ti6Al4V-0·1B ingot (Φ 300 mm) produced by vacuum arc remelting (VAR). It has been observed that the structure of Ti6Al4V-0·1B ingot in this experiment is not similar as that of earlier papers. The grain size in the centre of the ingot is 10 times larger than that of grains on the edge. This is because of the cooling speed of ingot as the edge cools faster than the centre in the process of VAR. Furthermore, this paper analysed the transverse and longitudinal tensile properties of Ti6Al4V-0·1B bar (Φ 100 mm) produced by free forging, which found that the transverse tensile elongation is only half of the longitudinal. Lots of TiB rods in transverse fracture were found, but not in longitudinal fracture. Microstructures of transverse and longitudinal bars were observed as well, which found TiB rods distributed along the axial, resulting in deterioration of the transverse tensile ductility.